Early versus late-onset major depression in the elderly: a comparative study - Ulrich, Luiz Eduardo Flores; Nogueira, Eduardo Lopes; Teixeira, Laura Mocellin; Ely, Luísa Scheer; Filho, José Celestino Borges; Neto, Alfredo Cataldo (PAJAR - Pan-American Journal of Aging Research, 2013)
Aims: This study aims to investigate the distinctive characteristics between elderly with early-onset and late-onset major depression with respect to sociodemographic factors, self-perceived health, cardiovascular risk factors, MMSE scores, family history of depression, depressive symptoms, melancholic features, suicide risk and alcohol abuse/dependence. Methods: Cross-sectional, descriptive and analytic study, with prospective data collection, in an random sample of 348 elderly people (≥60 years old) of the Family Heath Strategy, of which were identified 90 cases of DSM-IV unipolar major depression; subjects were divided according to early or late (≥60) age at onset of depression. Results: The prevalence of major depression in the whole sample was 25.86%. The elderly subjects with depression were mainly of early-onset (69.14%) and female (74.4%); the mean age in years was higher in the late-onset major depression group (p=0.028); the groups did not differ with respect to the other factors; after multivariate analysis there was a trend toward a negative association between suicide risk and late-onset depression. Conclusion: The early or late age at onset of depressive symptoms was not associated with different profiles. The results of this paper give support to the hypothesis that early-and late-onset major depressive disorders are clinically undistinguishable and do not represent distinct pathologies or subtypes.